Application of lithium dodecyl sulfate in improving damp-heat aging resistance of PC / ABS (polycarbonate / acrylonitrile-butadiene-styrene) alloy material

By adding lithium dodecyl sulfate to the PC/ABS alloy material, the problem of poor moisture and heat resistance in humid and heat environments is solved, the effect of improving the flame retardant performance and impact strength of the material is achieved, and the service life of the material is extended.

CN119912800APending Publication Date: 2025-05-02TIANJIN KINGFA NEW MATERIAL
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411979984.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

PC/ABS alloy materials have poor humidity and heat aging resistance in humid and heat environments, especially the flame retardant performance and impact strength after humid and heat aging have significantly decreased, which affects its widespread application.

Method used

Lithium dodecyl sulfate is added to the PC/ABS alloy material. Due to its hydrophilicity and lubricity, lithium dodecyl sulfate migrates to the surface of the material in a humid and heat environment, creating a weak acidic environment, improving the stability of PC resin and ABS resin, thereby improving the material's moisture and heat aging resistance.

Benefits of technology

By adding lithium dodecyl sulfate, the moisture-heat aging resistance of PC/ABS alloy materials is significantly improved, including maintaining a high flame retardant grade and impact strength, and extending the service life of the material in humid and heat environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005221317800000051
    Figure BDA0005221317800000051
  • Figure BDA0005221317800000061
    Figure BDA0005221317800000061
  • Figure BDA0005221317800000062
    Figure BDA0005221317800000062
Patent Text Reader

Abstract

The invention relates to application of lithium dodecyl sulfate to improvement of damp-heat aging resistance of a PC / ABS alloy material. The lithium dodecyl sulfate is added into the PC / ABS alloy material, and the lithium dodecyl sulfate can improve the damp-heat aging resistance of the PC / ABS alloy material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of polymer material modification, and more specifically, to the application of lithium dodecyl sulfate in improving the wet heat aging resistance of PC / ABS alloy materials. Background Art

[0002] Polycarbonate resin (PC) is a thermoplastic engineering plastic with excellent physical and mechanical properties, but its processing performance is poor. Generally, ABS is added to improve its processing performance, and the resulting material is usually called PC / ABS alloy.

[0003] PC / ABS alloy combines the excellent properties of two materials, including the moldability of acrylonitrile-butadiene-styrene copolymer and the mechanical properties and temperature resistance of polycarbonate. It can be widely used in automotive interior parts, business machines, communication equipment, household appliances and lighting equipment.

[0004] However, PC resin has poor hydrolysis resistance and is prone to hydrolysis in a wet and hot environment; while ABS has a PB rubber phase, which is prone to aging under the action of heat and catalyzes aging with the hydrolyzed PC resin. Therefore, the PC / ABS alloy has poor resistance to wet and hot aging, especially the flame retardant properties and impact strength after wet and hot aging. This problem has gradually affected the widespread application of PC / ABS alloys. Summary of the invention

[0005] The primary purpose of the present invention is to overcome the problem of poor moisture and heat aging resistance of the above-mentioned existing PC / ABS alloy, and to provide an application of lithium dodecyl sulfate in improving the moisture and heat aging resistance of PC / ABS alloy materials. In the present invention, lithium dodecyl sulfate is added to the PC / ABS alloy material, and lithium dodecyl sulfate can improve the moisture and heat aging resistance of the PC / ABS alloy material.

[0006] A further object of the present invention is to provide the above-mentioned PC / ABS alloy material.

[0007] A further object of the present invention is to provide a method for preparing the above PC / ABS alloy material.

[0008] A further object of the present invention is to provide an application of the above PC / ABS alloy material in improving the moisture-heat aging resistance of the PC / ABS alloy material.

[0009] The above-mentioned object of the present invention is achieved by the following technical solutions:

[0010] Application of lithium dodecyl sulfate in improving the moisture and heat aging resistance of PC / ABS alloy materials.

[0011] The inventors of the present invention have found that adding lithium dodecyl sulfate to PC / ABS alloy material can improve the moisture-heat aging resistance of PC / ABS alloy material. The reason may be that lithium dodecyl sulfate migrates to the surface of PC / ABS alloy material due to its hydrophilicity and lubricity in a moist and hot environment and creates a certain weakly acidic environment. The weakly acidic environment can enhance the stability of PC resin and ABS resin in PC / ABS alloy material, thereby improving the moisture-heat aging resistance of PC / ABS alloy material.

[0012] It should be understood that the PC in the PC / ABS alloy material refers to PC resin (polycarbonate resin), and ABS refers to ABS resin (acrylonitrile-butadiene-styrene copolymer).

[0013] Preferably, the moisture and heat aging resistance performance is the flame retardant performance after moisture and heat aging resistance and / or the impact strength after moisture and heat aging resistance.

[0014] Preferably, the mass ratio of PC resin, ABS resin and lithium dodecyl sulfate in the PC / ABS alloy material is (64-88):(4-16):(0.03-0.4).

[0015] Preferably, the number average molecular weight of the PC resin in the PC / ABS alloy material is between 20,000 and 40,000.

[0016] More preferably, the number average molecular weight of the PC resin in the PC / ABS alloy material is between 26,000 and 32,000.

[0017] By selecting PC resin within the number average molecular weight range, the resulting PC / ABS alloy material has a higher impact strength retention rate after wet heat aging.

[0018] In the present invention, the number average molecular weight of the PC resin can be measured according to GB / T 21864-2008.

[0019] Preferably, the melt index of the ABS resin in the PC / ABS alloy material measured at 220° C. and 10 kg is 5 to 35 g / 10 min. The melt index of the ABS resin can be measured according to ISO 1133-2011.

[0020] Preferably, the ABS resin in the PC / ABS alloy material has an acrylonitrile content of 10 to 30 wt %, a styrene content of 30 to 80 wt %, and a butadiene content of 10 to 30 wt %.

[0021] Preferably, the rubber phase content of the ABS resin in the PC / ABS alloy material is 10-30wt%.

[0022] Preferably, the mass percentage of lithium dodecyl sulfate in the PC / ABS alloy material is 0.04-0.4wt%, specifically 0.04wt%, 0.06wt%, 0.08wt%, 0.10wt%, 0.15wt%, 0.18wt%, 0.20wt%, 0.25wt%, 0.28wt%, 0.30wt%, 0.35wt% or 0.40wt%.

[0023] Preferably, the PC / ABS alloy material contains a flame retardant, and the mass ratio of the flame retardant to the PC resin in the PC / ABS alloy material is (6-12):(64-88).

[0024] A PC / ABS alloy material comprises the following components in parts by weight:

[0025] 64-88 parts of PC resin,

[0026] ABS resin 4-16 parts,

[0027] 0.03-0.4 parts of lithium dodecyl sulfate.

[0028] Specifically, the amount of PC resin used can be 64, 68, 72, 76, 80, 84 or 88 parts by weight. The amount of ABS resin used can be 4, 6, 8, 10, 12, 14 or 16 parts by weight. The amount of lithium dodecyl sulfate used can be 0.03, 0.04, 0.05, 0.08, 0.10, 0.12, 0.15, 0.18, 0.20, 0.22, 0.25, 0.28, 0.30, 0.35 or 0.40 parts by weight.

[0029] Preferably, the PC / ABS alloy material further comprises at least one of a flame retardant, a toughening agent, a lubricant, an antioxidant or an anti-dripping agent.

[0030] Usually, the flame retardant is used in an amount of 6 to 12 parts by weight, the toughening agent is used in an amount of 2 to 8 parts by weight, the lubricant is used in an amount of 0.1 to 2 parts by weight, the antioxidant is used in an amount of 0.1 to 2 parts by weight, and the anti-dripping agent is used in an amount of 0.1 to 2 parts by weight.

[0031] More preferably, the flame retardant includes but is not limited to phosphorus-based flame retardants (eg, phosphazene).

[0032] More preferably, the toughening agent includes but is not limited to a silicon-based toughening agent (eg, methyl methacrylate-acrylate-organic silicon copolymer).

[0033] Optionally, the antioxidant includes but is not limited to at least one of a hindered phenol antioxidant, a diphenylamine antioxidant, an amine antioxidant, a sodium hydrogen phosphate antioxidant or a phosphite.

[0034] Optionally, the lubricant includes but is not limited to at least one of a silicone lubricant, an ester lubricant, an amide lubricant or a polyethylene lubricant.

[0035] Optionally, the anti-drip agent includes but is not limited to polytetrafluoroethylene.

[0036] The preparation method of the PC / ABS alloy material comprises the following steps: mixing the components and melt-extruding to obtain the PC / ABS alloy material.

[0037] Preferably, the temperature of the melt extrusion is 220-270° C.; the screw aspect ratio of the extruder for the melt extrusion is 45-50:1, and the screw speed is 400-500 r / min.

[0038] The application of the above PC / ABS alloy material in the preparation of automobile parts, electronic parts or communication parts also falls within the protection scope of the present invention.

[0039] Compared with the prior art, the present invention has the following beneficial effects:

[0040] The invention adds lithium dodecyl sulfate into the PC / ABS alloy material, and the lithium dodecyl sulfate can improve the moisture-heat aging resistance of the PC / ABS alloy material. DETAILED DESCRIPTION

[0041] In the present invention, when it comes to a numerical interval (i.e., a numerical range), unless otherwise specified, the distribution of the optional numerical values ​​in the numerical interval is considered to be continuous, and includes the two numerical endpoints (i.e., the minimum value and the maximum value) of the numerical interval, and each numerical value between the two numerical endpoints. Unless otherwise specified, when the numerical interval only refers to the integers in the numerical interval, including the two endpoint integers of the numerical range, and each integer between the two endpoints, is equivalent to directly listing each integer. When multiple numerical ranges are provided to describe features or characteristics, these numerical ranges can be merged. In other words, unless otherwise specified, the numerical range disclosed herein should be understood to include any and all sub-ranges included therein. The "numerical value" in the numerical interval can be any quantitative value, such as a number, a percentage, a ratio, etc. "Numerical interval" allows broadly including numerical interval types such as percentage intervals, ratio intervals, and ratio intervals.

[0042] The mass or weight of the relevant components mentioned in the description of the embodiments of the present invention may not only refer to the specific content of each component, but also indicate the proportional relationship of the mass or weight between the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the description of the embodiments of the present invention, it is within the scope disclosed in the description of the embodiments of the present invention. Specifically, the mass or weight described in the description of the embodiments of the present invention may be units known in the chemical industry such as μg, mg, g, and kg.

[0043] In the present invention, if there are multiple steps involved in the method flow, unless otherwise specified herein, there is no strict order restriction on the execution of these steps, and they can be executed in other orders than described. Moreover, any step can include multiple sub-steps or multiple stages, and these sub-steps or stages are not necessarily executed at the same time, but can be executed at different times, and their execution order is not necessarily sequential, but can be executed in turn, alternating or simultaneously with other steps or parts of sub-steps or stages of other steps.

[0044] In order to more clearly and completely describe the technical solution of the present invention, the present invention is further described in detail through specific embodiments below. It should be understood that the specific embodiments described herein are only used to explain the present invention, and are not used to limit the present invention. Various changes can be made within the scope of the rights of the present invention.

[0045] Some of the reagents selected in the embodiments and comparative examples of the present invention are described as follows:

[0046] PC resin 1#: brand 1300-10NP, manufacturer LG, number average molecular weight 26500;

[0047] PC resin 2#: brand E-1000F, manufacturer Mitsubishi, number average molecular weight 32000;

[0048] ABS resin 1#: brand ABS 8391, manufacturer Gaoqiao Petrochemical, melt index 30.0g / 10min;

[0049] ABS resin 2#: brand ABS 8434, manufacturer Gaoqiao Petrochemical, melt index 15.0g / 10min;

[0050] ABS resin 3#: brand ABS 3504, manufacturer Gaoqiao Petrochemical, melt index 6.0g / 10min;

[0051] Lithium dodecyl sulfate: purity ≥99.0%, Shanghai Kanglang Biotechnology Co., Ltd.;

[0052] Sodium dodecyl sulfate: purity ≥99.0%, Shanghai Aladdin Biochemical Technology Co., Ltd.;

[0053] Toughening agent: Brand name is S-2001, manufacturer is Japan Mitsubishi Rayon, silicon-based toughening agent;

[0054] Flame retardant: brand name is SPB-100, manufacturer is Otsuka, Japan, phosphazene;

[0055] Other additives 1#: lubricant, PETS-AP, Italy Farge;

[0056] Unless otherwise specified, the components (eg, toughening agent, flame retardant, other auxiliary agent 1#) selected in each parallel example and comparative example are the same commercially available products.

[0057] The PC / ABS alloy materials provided in the embodiments and comparative examples of the present invention were tested for performance according to the following test methods:

[0058] (1) Flame retardant grade: tested in accordance with UL94; including initial flame retardant grade and flame retardant grade after damp heat aging; the damp heat aging treatment process is: the specimen is placed in an environment with a temperature of 85°C and a humidity of 85% for 1000 hours and then tested.

[0059] (2) Izod notched impact strength: tested in accordance with ASTM D256-10; including initial Izod notched impact strength and Izod notched impact strength after hygrothermal aging. The Izod notched impact strength retention rate is obtained by dividing the Izod notched impact strength after hygrothermal aging by the initial Izod notched impact strength. The hygrothermal aging treatment process is as follows: the specimens are placed in an environment with a temperature of 85° C. and a humidity of 85% for 1000 hours and then tested.

[0060] The PC / ABS alloy materials provided in the embodiments and comparative examples of the present invention are prepared as follows:

[0061] The components are weighed according to the formula, and the PC / ABS alloy material is obtained by melt-extrusion and granulation. Among them, the screw length-to-diameter ratio of the twin-screw extruder is 48:1; the screw speed is 450r / min, and the temperatures in each melting temperature zone are 230℃, 230℃, 230℃, 250℃, 260, 260℃, 260℃, 260℃, 260℃, 260℃, 260℃, and 260℃.

[0062] Examples 1 to 9 and Comparative Examples 1 to 2

[0063] Examples 1-9 and Comparative Examples 1-2 provide a series of PC / ABS alloy materials, whose formulas are shown in Table 1.

[0064] Table 1 Formulas of Examples 1 to 9 and Comparative Examples 1 to 2 (parts by weight)

[0065]

[0066]

[0067] The properties of the PC / ABS alloy materials of the embodiments and comparative examples were measured according to the above-mentioned test methods. The test results are shown in Table 2.

[0068] Table 2 Performance results of PC / ABS alloy materials of various embodiments and comparative examples

[0069]

[0070] From Table 2, we can see that:

[0071] After the PC / ABS alloy materials of Examples 1 to 9 were subjected to the wet heat aging treatment, the flame retardancy rating was still maintained above V-0, and the retention rate of the notched cantilever beam impact strength was above 87.0%, indicating that lithium dodecyl sulfate can improve the wet heat aging resistance of the PC / ABS alloy materials.

[0072] Comparative Example 1 does not add lithium dodecyl sulfate, and the flame retardant level of the PC / ABS alloy material after wet heat aging treatment is low, and the retention rate of the notched Izod impact strength is low. Comparative Example 2 adds sodium dodecyl sulfate, and the flame retardant level of the PC / ABS alloy material after wet heat aging treatment is low, and the retention rate of the notched Izod impact strength is low.

[0073] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. Application of lithium dodecyl sulfate in improving the moisture and heat aging resistance of PC / ABS alloy materials.

2. The application according to claim 1, characterized in that: The moisture-heat aging resistance performance is the flame retardant performance after moisture-heat aging resistance or the impact strength after moisture-heat aging resistance.

3. The application according to claim 1, characterized in that: The mass ratio of PC resin, ABS resin and lithium dodecyl sulfate in the PC / ABS alloy material is (64-88):(4-16):(0.03-0.4).

4. The use according to claim 1, characterized in that: The number average molecular weight of the PC resin in the PC / ABS alloy material is between 20,000 and 40,000.

5. The use according to claim 1, characterized in that: The melt index of the ABS resin in the PC / ABS alloy material measured at 220° C. and 10 kg is 5 to 35 g / 10 min.

6. The use according to claim 1, characterized in that: The mass percentage of lithium dodecyl sulfate in the PC / ABS alloy material is 0.04-0.4wt%.

7. A PC / ABS alloy material, characterized in that: The composition comprises the following components in parts by weight: 64-88 parts of PC resin, ABS resin 4-16 parts, 0.03-0.4 parts of lithium dodecyl sulfate.

8. The PC / ABS alloy material according to claim 7, characterized in that: The PC / ABS alloy material further comprises at least one of a flame retardant, a toughening agent, a lubricant, an antioxidant or an anti-dripping agent.

9. The method for preparing the PC / ABS alloy material according to any one of claims 7 to 8, characterized in that: The method comprises the following steps: mixing the components and performing melt extrusion to obtain the PC / ABS alloy material.

10. Use of the PC / ABS alloy material according to any one of claims 7 to 8 in the preparation of automobile parts, electronic parts or communication parts.